Massive Sternal Osteophyte Compressing Aortic Arch Branch Graft - Ellauzi, Hesham; Cardella, Jonathan; Zafar, Mohammad A.; Ziganshin, Bulat A.; Elefteriades, John A. (AORTA, 2021)
We present a dramatic computed tomography scan demonstrating compression of a brachiocephalic graft by a massive sternal osteophyte, coming to light many years after aortic arch replacement surgery.
Keywords: brachiocephalic artery; sternal osteophyte; stenosis